2021
DOI: 10.33182/ml.v18i6.1617
|View full text |Cite
|
Sign up to set email alerts
|

Post-Migration Fertility in Southern Europe: Romanian and Moroccan women in Italy and Spain

Abstract: This paper seeks to analyse migrant women’s reproductive behaviour in two countries with the lowest fertility rates, namely, Italy and Spain. We assess differences in migrant fertility patterns according to country of origin by comparing the post-migration motherhood of Moroccan and Romanian women. We have used data from the “2007 National Immigrant Survey” (INE) and the ”2011-2012 Survey on Social Integration and Condition among Foreign Citizens” (ISTAT) to adopt an event-history approach to the factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…This contrast between findings raises intriguing questions regarding the extent to which these explanations remain solid and valid when studying different origins and destinations, being FIs strongly related to the specificities of migratory projects and their conjunction and diversity in host countries. Thus, our results are clearly pointing out to the presence of gradients in the explanatory power of the adaptation hypothesis to differences in FIs across groups of women under observation, further supporting the idea of the presence of fertility differentials according to the heterogeneity of the characteristics of both the head and the migratory project (Impicciatore et al, 2020;Carella et al, 2021). In our analysis, the explanatory power of the adaptation theory to FIs of foreign women partnered to Italian men did change -as expected-but, somewhat surprisingly, this change was not large enough to cause the shift of the theory from adaptation to socialization.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This contrast between findings raises intriguing questions regarding the extent to which these explanations remain solid and valid when studying different origins and destinations, being FIs strongly related to the specificities of migratory projects and their conjunction and diversity in host countries. Thus, our results are clearly pointing out to the presence of gradients in the explanatory power of the adaptation hypothesis to differences in FIs across groups of women under observation, further supporting the idea of the presence of fertility differentials according to the heterogeneity of the characteristics of both the head and the migratory project (Impicciatore et al, 2020;Carella et al, 2021). In our analysis, the explanatory power of the adaptation theory to FIs of foreign women partnered to Italian men did change -as expected-but, somewhat surprisingly, this change was not large enough to cause the shift of the theory from adaptation to socialization.…”
Section: Discussionsupporting
confidence: 80%
“…FIs of foreign women partnered to Italian men will resemble those of foreign women partnered to foreign men if socialization holds; or, instead, will resemble those of Italian women partnered to Italian men, finding support for adaptation. Finally, as migrants' fertility is shaped by different norms or migratory projects (Impicciatore et al, 2020;Mussino et al, 2021;Alderotti and Trappolini, 2021;Carella et al, 2021;García-Pereiro and Paterno, 2022), we also hypothesize changes on the explanatory levels of Socialization vs Adaptation to FIs across different migrant origins of women partnered to Italian men.…”
Section: Theories and Hypothesesmentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, Rotella et al (2021) demonstrated that, in some countries observed in their study, the links between density and fertility were attenuated by key moderator variables such as religiousness and social norms. In accordance with these findings, we can assume that where population densities of foreigners are higher, cultural values and religious traditions could be stronger and more decisive in orienting reproductive behaviours, especially during the immediate post-settlement period in the host territory (Carella et al 2021;Mussino et al 2015;Mussino and Strozza 2012). Furthermore, the strength of ties and cultural norms is even more relevant among foreigners who intentionally opt for concentrated settlement patterns to ensure mutual support and to be cohesive in addressing the challenges produced by the environment and the host society.…”
Section: Discussionsupporting
confidence: 75%